Analysis of Booster Pump Power and Feasibility Using Total Head and NPSH Calculations on Triethylene Glycol (TEG) Circulation System of Project X in Offshore Fabrication Industry : Case Study at PT. NOV Profab Indonesia - Muhamad Agung; Abrar Ridwan (TURBO [Tulisan Riset Berbasis Online], 2026)
The Triethylene Glycol (TEG) circulation system functions to maintain the stability of the natural gas dehydration process by continuously circulating TEG from the surge drum to the process equipment. The booster pump plays a crucial role in sustaining the system’s flow rate and pressure to ensure optimal water vapor absorption. This study aims to calculate the total head of the system and evaluate the Net Positive Suction Head (NPSH) of the booster pump in the TEG circulation system at Project X, located at PT. NOV Profab Indonesia’s offshore fabrication facility. The calculation was performed using Bernoulli’s equation combined with major and minor head loss analysis, while the NPSHr (required) value was determined based on the HSVN (Head Suction Vapour Number) derived from the Cavitation Chart. The analysis results show that the total head of the system is 5.6 meters and the NPSHa (available) is 5.6 meters, which is higher than the NPSHr obtained from the HSVN data of 1.6 meters. Therefore, the pump operates safely without cavitation. These findings can serve as a reference for evaluating pump performance and as a design basis for TEG circulation systems in gas production facilities with similar characteristics.